Consanguinity and Risk of Congenital Heart Defects in Bangladesh - Al Mamun, Mohammad Abdullah; Hussain, Manzoor; Shahid Khan, Md Khalid Ebna (Dhaka Shishu (Children) Hospital Journal, 2022)
Background: Consanguineous marriage have been associated with an increased risk to various forms of inherited disease. Potential role of consanguinity in certain common birth defects is less clear especially with congenital heart defects (CHDs). Objective: This study was conducted to evaluate the potential role of consanguinity as a risk factor for congenital heart defects (CHDs) in Bangladesh. Methodology: It was a case control study, conducted from July 2018 to July 2019 at Dhaka Shishu (Children) Hospital. Parents of the children with CHD visited the outpatient department was considered as case. Control was taken from parents of the children who didn’t have congenital heart disease. Informed written consent was taken from parents. Data were collected by using a structured questionnaire containing all the variables of interest and analyzed by using SPSS version 21. Chi square test (S«2), Odds ratio (OR) and 95% confidence intervals (CIs) were calculated to estimate the associations between parental consanguinity and all CHDs. Risk factors on bivariate analysis were introduced into a logistic regression model as independent factors and dependent variable was CHDs to find out the association between CHDs and consanguinity. Results: Among study population consanguinity was present in 33(6.11%) cases. In the case group 23 children (8.85%) were born to consanguineous parents and in control group 10 children (3.57%) were born to consanguineous parents. CHDs were found significantly higher in children born to consanguineous parents (p<0.05). On logistic regression analysis consanguinity (p=0.02) was independently associated with CHDs. Children who born to consanguineous parents had 2.5 times risk of developing CHDs compared to those who were not born to consanguineous parents. Conclusions: Parental consanguinity is significantly associated with CHDs. DS (Child) H J 2021; 37(1): 34-39